PERSEPSI DOSEN ADMINISTRASI BISNIS TERHADAP PROGRAM AKREDITASI BAN-PT, KEMENTERIAN RISET, TEKNOLOGI, DAN PENDIDIKAN TINGGI - Umar - Farouk; Nur - Rini; Sandi Supaya; Sri Eka Sadriatwati (Politeknik Negeri Semarang, 2018)
This qualitative research is meant to describe the implementation of acrreditation program at Business Administration Department. The main issues discussed cover the knowlegde of facilitators about the program, the benefits of the program for stakeholders, the process of study program evaluation using BAN PT’s accreditation system, and the awareness of the importance of accreditation rank and the real quality of management and admimistration performance of Busuness Adminisration Department. All these are under the perception of Business Administration facilitators. This research uses purposive sampiling, The samples or informen are selected on the basis of some determined criteria. Data collection uses in depth interview, observation and literature study. The infomation resulted from the interview was put in a matrix table with the purpose to compare collected information from informan 1, 2, and 3. In this way the information was conluded systematically and regarded as valid and reliable data for the research. Data analysis was processed by following the steps recommended by Moleong, nemely data reduction, unit processing, categorization process, analysis, conclusion and recommendation. Based on the research it can be concluded that Business Administration Department facilitators perceived that accrediaion program at the department had been successfully done but there were some weaknesses whcih should be solved as recommended. The most important finding resulted from the research was the quality of study progams’ management and admiminstration was considered as more important than accreditation rank.